Anxiety, anxiety disorders, tobacco use, and nicotine a critical review of interrelationships. [article]. - Morissette, Sandra Baker
Smoking is highly prevalent across most anxiety disorders. Tobacco use increases risk for the later development of certain anxiety disorders, and smokers with anxiety disorders have more severe withdrawal symptoms during smoking cessation than smokers without anxiety disorders. The authors critically examined the relationships among anxiety, anxiety disorders, tobacco use, and nicotine dependence and reviewed the existing empirical literature. Future research is needed to better understand the interrelationships among these variables, including predictors, moderators, and mechanisms of action. Increased knowledge in these areas should inform prevention efforts as well as the development and improvement of smoking cessation programs for those with anxiety and other psychiatric disorders. -- (from the author)
Keywords: Anxiety; Anxiety disorders; Tobacco; Nicotine; Smoking